2-Step Murabaha as an alternative resource mobilisation tool for Islamic banks in the context of international trade. (3rd November 2009) - Gundogdu, Ahmet Suayb
This paper aims to show how to mobilise resources through Islamic financial instruments in the context of international trade. Throughout the paper there would be five entities namely, Bank-A, Bank-B, Bank-C, Importer and Exporter. Bank-A and Bank-B are recognised financial institutions and they operate internationally while the operations of Bank-C are limited to domestic market. It is Bank-B which mobilises resources from Bank-A through Mudaraba and alternative Reverse 2-Step Murabaha agreements. The details of disbursement for line of financing provided by Bank-B to Local Bank-C through 2-Step Murabaha Agreement are also provided for Letter of Credit and Documentary Collection settlements.